Irrigation increases on-farm soybean yields in water-limited environments without a trade-off in seed protein concentration - Carciocchi, Walter Daniel (2023)
Context or problem: A trade-off between seed protein concentration (SPC) and yield has been reported for soybean. Therefore, assessing management practices that can nullify this trade-off is relevant to avoid further declines in SPC in the future as yield continues to increase. While the positive effect of irrigation on yield is well documented, only a few studies have assessed the impact of irrigation on SPC, showing conflicting results. Objective or research question: The objective was to determine if the trade-off between seed yield and SPC persists when irrigation is applied and how management, soil, and weather factors influence the trade-off. We hypothesized that yield increases induced by irrigation would likely decrease SPC. Methods: Our experimental approach involved the use of producer-reported data, in-situ seed collection, and crop modeling. Yield and management data were collected from 268 soybean fields in Nebraska (USA), along with data on SPC, seed oil concentration (SOC), and seed carbohydrate concentration (SCC) determined from samples collected in each field. Field-specific phenological data were derived from model simulations. The combined data were then used to assess the effect of irrigation on seed yield and constituents as influenced by management, soil, and weather factors. Results: On average, both seed yield (+0.86 Mg ha−1) and SPC (+3.2 g kg−1) were higher, but SOC (–2.0 g kg−1) was lower, and SCC was unaffected in irrigated versus rainfed field pairs. Yield and SPC increased simultaneously in response to irrigation in two-thirds of the fields, especially when environmental conditions did not favor seed oil synthesis (e.g., cooler temperature and less incident solar radiation). A trade-off of higher seed yield and lower SPC occurred with irrigation in the remaining fields wherein conditions were favorable for seed oil synthesis (e.g., warmer temperatures and greater radiation). Conclusions: Despite higher seed yield generated in irrigated versus rainfed fields, no concurrent reduction occurred in SPC in the majority of irrigated fields – a surprising finding that was not consistent with the general expectation that higher soybean yields typically result in yield-SPC trade-off. Implications or significance: This study showed that irrigation-induced higher soybean yields are possible without an attendant SPC penalty when temperatures and radiation are conducive for its mitigation. We are unaware of any other yield-increasing practices – except nitrogen (N) fertilization - that do not result in a concomitant decline in SPC. A hypothesized higher N supply via soil N mineralization and/or biological N fixation in irrigated fields in this study may explain the absence of yield-protein trade-off.